Edukasi Spinal Anestesi Terhadap Pasien Pre Sectio Caesarea Menggunakan Media Audiovisual Guna Menurunkan Rasa Cemas - Khoirul Anam, Ahmad; Novitasari, Dwi; Yudha, Magenda Bisma (Yayasan Inspirasi El Burhani, 2024)
Introduction: A caesarean section is a surgical delivery technique in which the infant is removed through incisions in the mother's abdomen and uterus. Each delivery procedure might exert psychological effects on the mother, especially with anxiety. A non-pharmacological approach to mitigate anxiety involves educating patients about spinal anaesthesia with audiovisual materials. Objective: This community service project aims to provide education through audiovisual means to reduce tension and lower anxiety in pre-operative caesarean section patients undergoing spinal anesthesia. Method: The method involved delivering a 10-minute audiovisual education session to 30 participants and measuring anxiety using the APAIS tool in the labor ward. Result: The results show that the level of anxiety before the education was categorized as mild anxiety for 6 participants (20.0%), moderate anxiety for 15 participants (50.0%), severe anxiety for 6 participants (20.0%), and very severe anxiety for 3 participants (10.0%). After the education, the majority of participants reported mild anxiety at 17 (56.7%), moderate anxiety at 10 (33.7%), severe anxiety at 2 (6.7%), with no participants reporting very severe anxiety (0%), and 1 participant (3.3%) reported no anxiety. Conclusion: The conclusion of this community service project is that education on spinal anesthesia using audiovisual media is quite effective in reducing anxiety in pre-caesarean section patients